A validated uv spectrophotometric determination of an antivilral drug - adefovir dipivoxil from tablet formulations - R. VIJAY AMIRTHA RAJ,; SANDEEP.CH,; KRISHNA VAMSI MOVVA,; KALPANA.A, (International Journal of Pharma and Bio Sciences, 2011)
Simple, sensitive and specific spectrophotometric method was developed and validated for quantification of Adefovir dipivoxil in tabltet dosage form. Drug showed the absorption maxima in water at 260nm and was linear for a range of 2-10µg/ml with a correlation coefficient of 0.9999. The validation of the above method was done by carrying out precision and accuracy studies. The Limit of detection and Limit of Quantification for Adefovir dipivoxil was found to be 0.82mcg/ml and 2.76mcg/ml. The percentage recovery was found to be 99.3% and showed good repeatability with relative standard deviation less than 2. So, the proposed method can be applied for the routine analysis of Adefovir dipivoxil from formulations.